STUDY ON THE INFLUENCE OF LONG-TERM MONOCULTURE AND OF THREE TYPES OF CROP ROTATIONS ON WHEAT YIELD IN BURNAS PLAIN (ROMANIA) - Mihai BERCA; Valentina-Ofelia ROBESCU; Roxana HOROIAȘ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In sylvo-steppe conditions, on a leached chernozem with around 3.5% humus, 10 years experiments (2005-2014) were carried out on the yield of Josef premium wheat variety in monoculture (W-W-W-W), in crop rotation with two plants (W-W-M-M), in crop rotation with four different plants, but without ameliorative plant (W-R-M-SF) and crop rotation with peas as an ameliorative plant (P-W-R-W). After 10 years, wheat monoculture reduced production by 22 q/ha, i.e. 35% compared to the starting year. In the W-W-M-M crop rotation system, the yield loss was reduced by half (18.6%), while in the case of W-R-M-SF, wheat production remained constant throughout the entire experimentation period. The crop rotation system with peas (P-W-R-W) brought a very significant harvest increase after 10 years – 8.58 q/ha (12.1%). It is especially recommended the crop rotation system with the ameliorative plant, which obtains the highest yield (70.38 q/ha), followed by the one with different plants, which doesn’t reduce the production, but doesn’t raise it either. Under no circumstances, wheat monoculture mustn’t exceed 2-3 years.